High-bending-strength sintered neodymium-iron-boron magnet and preparation method thereof
Through hydrogen crushing, airflow grinding, press forming, sintering and aging treatment, sintering and high bending strength sintered NdFeB magnets were prepared, solving the problem of insufficient bending strength of NdFeB magnets and achieving performance improvement without changing magnetic properties.
Patent Information
- Application Number
- CN202510187012.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-20
- Publication Date
- 2025-04-18
AI Technical Summary
When the neodymium iron boron sintered permanent magnet rotates at high speed, it is prone to fracture due to centrifugal force and magnetic steel extrusion, resulting in insufficient bending strength and cannot meet the application requirements of many high-tech fields.
The sintered NdFeB magnet with high bending strength is prepared through hydrogen crushing, airflow grinding, press molding, sintering and aging treatment. The specific steps include vacuum smelting to obtain the NdFeB substrate alloy, performing rapid casting sheet preparation, hydrogen crushing, airflow grinding, orientation molding and isostatic pressure treatment, and finally sintering and aging treatment.
While maintaining the magnetic properties unchanged, the bending strength of neodymium iron boron magnets is significantly improved, its mechanical properties are improved, and application requirements in the field of high-tech.
Smart Images

Figure CN119852049A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of NdFeB magnet production, and in particular to a high-bending-strength sintered NdFeB magnet and a preparation method thereof. Background Art
[0002] NdFeB sintered permanent magnets are widely used in high-tech fields such as electronic information, medical equipment, new energy vehicles, household appliances, robots, etc. In most application fields, NdFeB sintered permanent magnets are loaded into the rotors of compressors and motors. When the compressors and motors rotate at high speed, the centrifugal force generated and the extrusion of the tooling and rotor magnets cause the NdFeB sintered permanent magnets to break. Therefore, improving the bending strength of NdFeB sintered permanent magnets is a major research hotspot.
[0003] The surface of NdFeB sintered permanent magnet is porous and sparse, and grinding is generally used for machining. If the thermal conductivity of the grinding wheel is poor, the local temperature of the NdFeB sintered permanent magnet will be too high, causing micro cracks, making the NdFeB sintered permanent magnet hard and brittle, and mechanical properties such as bending strength will also be reduced. However, in many application fields of NdFeB sintered permanent magnets, bending strength has become a benchmark acceptance standard. Therefore, it is particularly important to improve the bending strength of NdFeB sintered permanent magnets. Summary of the invention
[0004] In order to overcome the above-mentioned shortcomings, the purpose of the present invention is to provide a sintered NdFeB magnet with high bending strength, and also provide a method for preparing the sintered NdFeB magnet with high bending strength. The prepared NdFeB magnet has little change in magnetic properties and improved bending strength after hydrogen crushing, air flow grinding, pressing, sintering and aging treatment.
[0005] The technical solution of the present invention to solve the technical problem is: A high bending strength sintered NdFeB magnet having the general formula: (Pr f Nd g ) a Co b Cu c M d B e Fe 100-a-b-c-d-e-f ; Wherein, a, b, c, d, e, f, g are mass percentages, 29.5≤a≤30.5, 0≤b≤2.5, 0.1≤c≤0.4, 0<d≤3, 0.9≤e≤1, f:g=23~28:72~77; M is a combination of two or more of Al, Cr, Nb, Zr, Ga, Ti, Mn, Zn, V, and Mo and must contain Ga.
[0006] As an improvement of the present invention, it has the general formula: (Pr f Nd g ) a Co b Cu c M d B e Fe 100-a-b-c-d-e-f ; Wherein, a, b, c, d, e, f, g are mass percentages, 29.5≤a≤30.5, 0≤b≤2.5, 0.1≤c≤0.4, 0<d≤3, 0.9≤e≤1, f:g=23~28:72~77; M is Zr, Ti and Ga, and Zr:Ti=1:1, Cu:Ga=2.22:1.
[0007] As an improvement of the present invention, it has the general formula: (Pr f Nd g ) a Co b Cu c M d B e Fe 100-a-b-c-d-e-f ; Wherein, a, b, c, d, e, f, g are mass percentages, 29.5≤a≤30.5, 0≤b≤2.5, 0.1≤c≤0.4, 0<d≤3, 0.9≤e≤1, f:g=23~28:72~77; M is Zr, Ti and Ga, and Zr:Ti=1:2.
[0008] As an improvement of the present invention, it has the general formula: (Pr f Nd g ) a Co b Cu c M d B e Fe 100-a-b-c-d-e-f ; Wherein, a, b, c, d, e, f, g are mass percentages, 29.5≤a≤30.5, 0≤b≤2.5, 0.1≤c≤0.4, 0<d≤3, 0.9≤e≤1, f:g=23~28:72~77; M is Zr, Ti and Ga, and Cu:Ga=1:1.
[0009] A method for preparing a sintered NdFeB magnet with high bending strength, comprising the following steps: S1. Obtaining a NdFeB base alloy by vacuum melting, wherein the general chemical formula of the NdFeB base alloy is: (Pr f Nd g ) a Co b Cu c M d B e Fe 100-a-b-c-d-e-f ; Wherein, a, b, c, d, e, f, g are mass percentages, 29.5≤a≤30.5, 0≤b≤2.5, 0.1≤c≤0.4, 0<d≤3, 0.9≤e≤1, f:g=23~28:72~77; M is a combination of two or more of Al, Cr, Nb, Zr, Ga, Ti, Mn, Zn, V, Mo and must contain Ga; S2, placing the NdFeB base alloy obtained in step S1 into a rapid solidification furnace crucible for smelting, and then rapidly quenching to obtain a rapid solidification casting sheet; S3, placing the rapidly solidified casting sheet into a hydrogen crushing furnace, performing dehydrogenation treatment, and cooling to obtain a coarse powder; S4, mixing the coarse powder with the antioxidant, stirring evenly with a three-dimensional mixer, and then jet milling to obtain fine powder with a particle size of 3.7um to 4.6um, adding a lubricant to the fine powder, and stirring evenly with a three-dimensional mixer; S5, orienting the fine powder with lubricant added in a nitrogen atmosphere with a magnetic field strength of 1.5T to 2.2T, and then isostatically pressing to obtain a green body; S6. The green body is subjected to sintering and aging treatment to obtain a sintered NdFeB magnet.
[0010] As an improvement of the present invention, in step S1, the general chemical formula of the NdFeB substrate alloy is: (Pr f Nd g ) a Co b Cu c M d B e Fe 100-a-b-c-d-e-f ; Wherein, a, b, c, d, e, f, g are mass percentages, 29.5≤a≤30.5, 0≤b≤2.5, 0.1≤c≤0.4, 0<d≤3, 0.9≤e≤1, f:g=23~28:72~77; M is Zr, Ti and Ga, and Zr:Ti=1:1, Cu:Ga=2.22:1.
[0011] As an improvement of the present invention, in step S1, the general chemical formula of the NdFeB substrate alloy is: (Pr f Nd g ) a Co b Cuc M d B e Fe 100-a-b-c-d-e-f ; Wherein, a, b, c, d, e, f, g are mass percentages, 29.5≤a≤30.5, 0≤b≤2.5, 0.1≤c≤0.4, 0<d≤3, 0.9≤e≤1, f:g=23~28:72~77; M is Zr, Ti and Ga, and Zr:Ti=1:2.
[0012] As an improvement of the present invention, in step S1, the general chemical formula of the NdFeB substrate alloy is: (Pr f Nd g ) a Co b Cu c M d B e Fe 100-a-b-c-d-e-f ; Wherein, a, b, c, d, e, f, g are mass percentages, 29.5≤a≤30.5, 0≤b≤2.5, 0.1≤c≤0.4, 0<d≤3, 0.9≤e≤1, f:g=23~28:72~77; M is Zr, Ti and Ga, and Cu:Ga=1:1.
[0013] As a further improvement of the present invention, in step S4, a portion of the coarse powder is mixed with 0.05%~0.1% antioxidant, and after being uniformly stirred in a three-dimensional mixer, it is subjected to air flow milling under the condition that the oxidizing gas content is 0ppm, and after being crushed, a mixed fine powder 1 with a particle size of 3.8±0.1um is obtained; at the same time, another portion of the coarse powder is mixed with 0.05%~0.1% antioxidant, and after being uniformly stirred in a three-dimensional mixer, it is subjected to air flow milling under the condition that the oxidizing gas content is 0ppm, and after being crushed, a mixed fine powder 2 with a particle size of 4.5±0.1um is obtained; the mixed fine powder 1 and the mixed fine powder 2 are mixed in a weight percentage of 1:1, and then 0.05%~0.1% of a lubricant is added, and the mixture is uniformly stirred in a three-dimensional mixer.
[0014] As a further improvement of the present invention, in step S5, the fine powder to which the lubricant is added is oriented and formed in a magnetic field strength of 1.5T~2.2T and a nitrogen protective atmosphere, and isostatically pressed at a pressure of 140MPa~220MPa to obtain a green body; in step S6, the green body is vacuum sintered at a sintering temperature of 1045℃~1065℃ and a holding time of 6h~10h, and then aged to obtain a sintered NdFeB magnet.
[0015] The present invention has the following advantages: 1. After hydrogen crushing, air flow grinding, pressing, sintering and aging treatment, the magnetic properties do not change much and the bending strength is improved; 2. Under the premise of not changing the components of NdFeB sintered permanent magnets, by designing different particle sizes and coordinating multiple powder particle sizes, after oriented pressing, high-temperature sintering and aging treatment, a sintered NdFeB magnet with stronger bending strength was obtained.
[0016] 3. The present invention involves only one kind of raw material, quick-setting casting sheet and coarse powder, and the process is simple. There is no need to perform multiple smelting and hydrogen crushing to prepare coarse powder. A single powder particle size increase can greatly improve the bending strength without changing the magnet performance. The operation is simple for production personnel and the production feasibility is extremely high. If a NdFeB magnet with higher bending strength is to be obtained, the ratio of powders of various powder particle sizes is also highly operable, and the particle size is coarser and the safety is higher. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The table and graph of the magnetic properties and bending strength results of the blanks of Examples 1 to 10 of the present invention; Figure 2 This is a table showing the magnetic properties and bending strength results after grain boundary penetration of Examples 1 to 10 of the present invention. DETAILED DESCRIPTION
[0019] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments and drawings described herein are only used to explain the present invention and are not used to limit the present invention.
[0020] The method for preparing the high bending strength sintered NdFeB magnet of the present invention provides the following embodiments: Embodiment 1 comprises the following steps: S1. Obtaining a NdFeB base alloy by vacuum melting, wherein the general chemical formula of the NdFeB base alloy is: (Pr f Nd g ) a Co b Cu c M d B e Fe 100-a-b-c-d-e-f ; Wherein, a, b, c, d, e, f, g are mass percentages, 29.5≤a≤30.5, 0≤b≤2.5, 0.1≤c≤0.4, 0<d≤3, 0.9≤e≤1, f:g=23~28:72~77; M is Zr, Ti and Ga, and Zr:Ti=1:1, Cu:Ga=2.22:1; S2. Place the NdFeB base alloy into a quick-setting furnace crucible for smelting. Then, under the protection of inert gas argon, place it in an induction furnace at 1480±20℃ and a vacuum degree of 2~10×10-2 Pa conditions, and then rapidly quenched and spun at 1425±20℃ to form a quick-solidified casting sheet with a thickness of 0.28±0.05mm; S3, placing the quick-solidification casting sheet into a hydrogen crushing furnace, absorbing hydrogen at a pressure of 0-2MPa for 2-4h, then dehydrogenating at a temperature of 500-600°C for 6-10h, and finally cooling to obtain coarse powder; S4, adding 0.05-0.1% antioxidant to the coarse powder, stirring it evenly with a three-dimensional mixer and then jet milling it, the jet milling is carried out under the condition that the oxidizing gas content is 0ppm, and the fine powder with a particle size of 3.8±0.1um is obtained after the pulverization, and then adding 0.05-0.1% lubricant, stirring it evenly with a three-dimensional mixer and then pressing it into shape; S5, orienting the fine powder in a nitrogen atmosphere with a magnetic field strength of 1.5T to 2.2T, and isostatically pressing the fine powder under a pressure of 140 to 220MPa to obtain a green body; S6. The green body is subjected to sintering and aging treatment. The green body is vacuum sintered at a sintering temperature of 1045-1065°C and a holding time of 6-10 hours. The green body is then subjected to aging treatment. The aging treatment is a two-stage aging treatment. The primary aging treatment has a temperature of 850-920°C and a holding time of 3-5 hours. The secondary aging treatment has a temperature of 480-520°C and a holding time of 3-5 hours. Thus, a sintered NdFeB magnet is obtained.
[0021] Embodiment 2 comprises the following steps: S1. Obtaining a NdFeB base alloy by vacuum melting, wherein the general chemical formula of the NdFeB base alloy is: (Pr f Nd g ) a Co b Cu c M d B e Fe 100-a-b-c-d-e-f ; Wherein, a, b, c, d, e, f, g are mass percentages, 29.5≤a≤30.5, 0≤b≤2.5, 0.1≤c≤0.4, 0<d≤3, 0.9≤e≤1, f:g=23~28:72~77; M is Zr, Ti and Ga, and Zr:Ti=1:1, Cu:Ga=2.22:1; S2. Place the NdFeB base alloy into a quick-setting furnace crucible for smelting. Then, under the protection of inert gas argon, place it in an induction furnace at 1480±20℃ and a vacuum degree of 2~10×10 -2 Pa conditions, and then rapidly quenched and spun at 1425±20℃ to form a quick-solidified casting sheet with a thickness of 0.28±0.05mm; S3, placing the quick-solidification casting sheet into a hydrogen crushing furnace, absorbing hydrogen at a pressure of 0-2MPa for 2-4h, then dehydrogenating at a temperature of 500-600°C for 6-10h, and finally cooling to obtain coarse powder; S4, adding 0.05-0.1% antioxidant to the coarse powder, stirring it evenly with a three-dimensional mixer and then jet milling it. The jet milling is carried out under the condition that the oxidizing gas content is 0ppm. After the pulverization, fine powder with a particle size of 4.5±0.1um is obtained. Then, 0.05-0.1% lubricant is added, stirring it evenly with a three-dimensional mixer and then pressing and molding it; S5, orienting the fine powder in a nitrogen atmosphere with a magnetic field strength of 1.5T to 2.2T, and isostatically pressing the fine powder under a pressure of 140 to 220MPa to obtain a green body; S6. The green body is subjected to sintering and aging treatment. The green body is vacuum sintered at a sintering temperature of 1045-1065°C and a holding time of 6-10 hours. The green body is then subjected to aging treatment. The aging treatment is a two-stage aging treatment. The primary aging treatment has a temperature of 850-920°C and a holding time of 3-5 hours. The secondary aging treatment has a temperature of 480-520°C and a holding time of 3-5 hours. Thus, a sintered NdFeB magnet is obtained.
[0022] Embodiment 3 comprises the following steps: S1. Obtaining a NdFeB base alloy by vacuum melting, wherein the general chemical formula of the NdFeB base alloy is: (Pr f Nd g ) a Co b Cu c M d B e Fe 100-a-b-c-d-e-f ; Wherein, a, b, c, d, e, f, g are mass percentages, 29.5≤a≤30.5, 0≤b≤2.5, 0.1≤c≤0.4, 0<d≤3, 0.9≤e≤1, f:g=23~28:72~77; M is Zr, Ti and Ga, and Zr:Ti=1:2; S2. Place the NdFeB base alloy into a quick-setting furnace crucible for smelting. Then, under the protection of inert gas argon, place it in an induction furnace at 1480±20℃ and a vacuum degree of 2~10×10 -2 Pa conditions, and then rapidly quenched and spun at 1425±20℃ to form a quick-solidified casting sheet with a thickness of 0.28±0.05mm; S3, placing the quick-solidification casting sheet into a hydrogen crushing furnace, absorbing hydrogen at a pressure of 0-2MPa for 2-4h, then dehydrogenating at a temperature of 500-600°C for 6-10h, and finally cooling to obtain coarse powder; S4, adding 0.05-0.1% antioxidant to the coarse powder, stirring it evenly with a three-dimensional mixer and then jet milling it, the jet milling is carried out under the condition that the oxidizing gas content is 0ppm, and the fine powder with a particle size of 3.8±0.1um is obtained after the pulverization, and then adding 0.05-0.1% lubricant, stirring it evenly with a three-dimensional mixer and then pressing it into shape; S5, orienting the fine powder in a nitrogen atmosphere with a magnetic field strength of 1.5T to 2.2T, and isostatically pressing the fine powder under a pressure of 140 to 220MPa to obtain a green body; S6. The green body is subjected to sintering and aging treatment. The green body is vacuum sintered at a sintering temperature of 1045-1065°C and a holding time of 6-10 hours. The green body is then subjected to aging treatment. The aging treatment is a two-stage aging treatment. The primary aging treatment has a temperature of 850-920°C and a holding time of 3-5 hours. The secondary aging treatment has a temperature of 480-520°C and a holding time of 3-5 hours. Thus, a sintered NdFeB magnet is obtained.
[0023] Embodiment 4 comprises the following steps: S1. Obtaining a NdFeB base alloy by vacuum melting, wherein the general chemical formula of the NdFeB base alloy is: (Pr f Nd g ) a Co b Cu c M d B e Fe 100-a-b-c-d-e-f ; Wherein, a, b, c, d, e, f, g are mass percentages, 29.5≤a≤30.5, 0≤b≤2.5, 0.1≤c≤0.4, 0<d≤3, 0.9≤e≤1, f:g=23~28:72~77; M is Zr, Ti and Ga, and Zr:Ti=1:2; S2. Place the NdFeB base alloy into a quick-setting furnace crucible for smelting. Then, under the protection of inert gas argon, place it in an induction furnace at 1480±20℃ and a vacuum degree of 2~10×10 -2 Pa conditions, and then rapidly quenched and spun at 1425±20℃ to form a quick-solidified casting sheet with a thickness of 0.28±0.05mm; S3, placing the quick-solidification casting sheet into a hydrogen crushing furnace, absorbing hydrogen at a pressure of 0-2MPa for 2-4h, then dehydrogenating at a temperature of 500-600°C for 6-10h, and finally cooling to obtain coarse powder; S4, adding 0.05-0.1% antioxidant to the coarse powder, stirring it evenly with a three-dimensional mixer and then jet milling it. The jet milling is carried out under the condition that the oxidizing gas content is 0ppm. After the pulverization, fine powder with a particle size of 4.5±0.1um is obtained. Then, 0.05-0.1% lubricant is added, stirring it evenly with a three-dimensional mixer and then pressing and molding it; S5, orienting the fine powder in a nitrogen atmosphere with a magnetic field strength of 1.5T to 2.2T, and isostatically pressing the fine powder under a pressure of 140 to 220MPa to obtain a green body; S6. The green body is subjected to sintering and aging treatment. The green body is vacuum sintered at a sintering temperature of 1045-1065°C and a holding time of 6-10 hours. The green body is then subjected to aging treatment. The aging treatment is a two-stage aging treatment. The primary aging treatment has a temperature of 850-920°C and a holding time of 3-5 hours. The secondary aging treatment has a temperature of 480-520°C and a holding time of 3-5 hours. Thus, a sintered NdFeB magnet is obtained.
[0024] Embodiment 5 comprises the following steps: S1. Obtaining a NdFeB base alloy by vacuum melting, wherein the general chemical formula of the NdFeB base alloy is: (Pr f Nd g ) a Co b Cu c M d B e Fe 100-a-b-c-d-e-f ; Wherein, a, b, c, d, e, f, g are mass percentages, 29.5≤a≤30.5, 0≤b≤2.5, 0.1≤c≤0.4, 0<d≤3, 0.9≤e≤1, f:g=23~28:72~77; M is Zr, Ti and Ga, and Cu:Ga=1:1; S2. Place the NdFeB base alloy into a quick-setting furnace crucible for smelting. Then, under the protection of inert gas argon, place it in an induction furnace at 1480±20℃ and a vacuum degree of 2~10×10 -2 Pa conditions, and then rapidly quenched and spun at 1425±20℃ to form a quick-solidified casting sheet with a thickness of 0.28±0.05mm; S3, placing the quick-solidification casting sheet into a hydrogen crushing furnace, absorbing hydrogen at a pressure of 0-2MPa for 2-4h, then dehydrogenating at a temperature of 500-600°C for 6-10h, and finally cooling to obtain coarse powder; S4, adding 0.05-0.1% antioxidant to the coarse powder, stirring it evenly with a three-dimensional mixer and then jet milling it, the jet milling is carried out under the condition that the oxidizing gas content is 0ppm, and the fine powder with a particle size of 3.8±0.1um is obtained after the pulverization, and then adding 0.05-0.1% lubricant, stirring it evenly with a three-dimensional mixer and then pressing it into shape; S5, orienting the fine powder in a nitrogen atmosphere with a magnetic field strength of 1.5T to 2.2T, and isostatically pressing the fine powder under a pressure of 140 to 220MPa to obtain a green body; S6. The green body is subjected to sintering and aging treatment. The green body is vacuum sintered at a sintering temperature of 1045-1065°C and a holding time of 6-10 hours. The green body is then subjected to aging treatment. The aging treatment is a two-stage aging treatment. The primary aging treatment has a temperature of 850-920°C and a holding time of 3-5 hours. The secondary aging treatment has a temperature of 480-520°C and a holding time of 3-5 hours. Thus, a sintered NdFeB magnet is obtained.
[0025] Embodiment 6 comprises the following steps: S1. Obtaining a NdFeB base alloy by vacuum melting, wherein the general chemical formula of the NdFeB base alloy is: (Pr f Nd g ) a Co b Cu c M d B e Fe 100-a-b-c-d-e-f ; Wherein, a, b, c, d, e, f, g are mass percentages, 29.5≤a≤30.5, 0≤b≤2.5, 0.1≤c≤0.4, 0<d≤3, 0.9≤e≤1, f:g=23~28:72~77; M is Zr, Ti and Ga, and Cu:Ga=1:1; S2. Place the NdFeB base alloy into a quick-setting furnace crucible for smelting. Then, under the protection of inert gas argon, place it in an induction furnace at 1480±20℃ and a vacuum degree of 2~10×10 -2 Pa conditions, and then rapidly quenched and spun at 1425±20℃ to form a quick-solidified casting sheet with a thickness of 0.28±0.05mm; S3, placing the quick-solidification casting sheet into a hydrogen crushing furnace, absorbing hydrogen at a pressure of 0-2MPa for 2-4h, then dehydrogenating at a temperature of 500-600°C for 6-10h, and finally cooling to obtain coarse powder; S4, adding 0.05-0.1% antioxidant to the coarse powder, stirring it evenly with a three-dimensional mixer and then jet milling it. The jet milling is carried out under the condition that the oxidizing gas content is 0ppm. After the pulverization, fine powder with a particle size of 4.5±0.1um is obtained. Then, 0.05-0.1% lubricant is added, stirring it evenly with a three-dimensional mixer and then pressing and molding it; S5, orienting the fine powder in a nitrogen atmosphere with a magnetic field strength of 1.5T to 2.2T, and isostatically pressing the fine powder under a pressure of 140 to 220MPa to obtain a green body; S6. The green body is subjected to sintering and aging treatment. The green body is vacuum sintered at a sintering temperature of 1045-1065°C and a holding time of 6-10 hours. The green body is then subjected to aging treatment. The aging treatment is a two-stage aging treatment. The primary aging treatment has a temperature of 850-920°C and a holding time of 3-5 hours. The secondary aging treatment has a temperature of 480-520°C and a holding time of 3-5 hours. Thus, a sintered NdFeB magnet is obtained.
[0026] Embodiment 7 comprises the following steps: S1. Obtaining a NdFeB base alloy by vacuum melting, wherein the general chemical formula of the NdFeB base alloy is: (Pr f Nd g ) a Co b Cu c M d B e Fe 100-a-b-c-d-e-f ; Wherein, a, b, c, d, e, f, g are mass percentages, 29.5≤a≤30.5, 0≤b≤2.5, 0.1≤c≤0.4, 0<d≤3, 0.9≤e≤1, f:g=23~28:72~77; M is Zr, Ti and Ga, and Zr:Ti=1:1, Cu:Ga=2.22:1; S2. Place the NdFeB base alloy into a quick-setting furnace crucible for smelting. Then, under the protection of inert gas argon, place it in an induction furnace at 1480±20℃ and a vacuum degree of 2~10×10 -2 Pa conditions, and then rapidly quenched and spun at 1425±20℃ to form a quick-solidified casting sheet with a thickness of 0.28±0.05mm; S3, placing the quick-solidification casting sheet into a hydrogen crushing furnace, absorbing hydrogen at a pressure of 0-2MPa for 2-4h, then dehydrogenating at a temperature of 500-600°C for 6-10h, and finally cooling to obtain coarse powder; S4, mixing a portion of the coarse powder with 0.05%~0.1% antioxidant, stirring evenly with a three-dimensional mixer, and then jet milling under the condition that the oxidizing gas content is 0ppm, and then crushing to obtain a mixed fine powder 1 with a particle size of 3.8±0.1um; at the same time, mixing another portion of the coarse powder with 0.05%~0.1% antioxidant, stirring evenly with a three-dimensional mixer, and then jet milling under the condition that the oxidizing gas content is 0ppm, and then crushing to obtain a mixed fine powder 2 with a particle size of 4.5±0.1um; the mixed fine powder 1 and the mixed fine powder 2 are mixed in a weight percentage of 1:1, and then 0.05%~0.1% lubricant is added, and the mixture is stirred evenly with a three-dimensional mixer for pressing and molding; S5, orienting and molding the mixed fine powder 1 and the fine powder 2 in a nitrogen protective atmosphere at a magnetic field strength of 1.5T to 2.2T, and then isostatically pressing the mixed fine powder 1 and the mixed fine powder 2 at a pressure of 140 to 220 MPa to obtain a green body; S6. The green body is subjected to sintering and aging treatment. The green body is vacuum sintered at a sintering temperature of 1045-1065°C and a holding time of 6-10 hours. The green body is then subjected to aging treatment. The aging treatment is a two-stage aging treatment. The primary aging treatment has a temperature of 850-920°C and a holding time of 3-5 hours. The secondary aging treatment has a temperature of 480-520°C and a holding time of 3-5 hours. Thus, a sintered NdFeB magnet is obtained.
[0027] Embodiment 8 comprises the following steps: S1. Obtaining a NdFeB base alloy by vacuum melting, wherein the general chemical formula of the NdFeB base alloy is: (Pr f Nd g ) a Co b Cu c M d B e Fe 100-a-b-c-d-e-f ; Wherein, a, b, c, d, e, f, g are mass percentages, 29.5≤a≤30.5, 0≤b≤2.5, 0.1≤c≤0.4, 0<d≤3, 0.9≤e≤1, f:g=23~28:72~77; M is Zr, Ti and Ga, and Zr:Ti=1:2; S2. Place the NdFeB base alloy into a quick-setting furnace crucible for smelting. Then, under the protection of inert gas argon, place it in an induction furnace at 1480±20℃ and a vacuum degree of 2~10×10 -2 Pa conditions, and then rapidly quenched and spun at 1425±20℃ to form a quick-solidified casting sheet with a thickness of 0.28±0.05mm; S3, placing the quick-solidification casting sheet into a hydrogen crushing furnace, absorbing hydrogen at a pressure of 0-2MPa for 2-4h, then dehydrogenating at a temperature of 500-600°C for 6-10h, and finally cooling to obtain coarse powder; S4, mixing a portion of the coarse powder with 0.05%~0.1% antioxidant, stirring evenly with a three-dimensional mixer, and then jet milling under the condition that the oxidizing gas content is 0ppm, and then crushing to obtain a mixed fine powder 1 with a particle size of 3.8±0.1um; at the same time, mixing another portion of the coarse powder with 0.05%~0.1% antioxidant, stirring evenly with a three-dimensional mixer, and then jet milling under the condition that the oxidizing gas content is 0ppm, and then crushing to obtain a mixed fine powder 2 with a particle size of 4.5±0.1um; the mixed fine powder 1 and the mixed fine powder 2 are mixed in a weight percentage of 1:1, and then 0.05%~0.1% lubricant is added, and the mixture is stirred evenly with a three-dimensional mixer for pressing and molding; S5, orienting and molding the mixed fine powder 1 and the fine powder 2 in a nitrogen protective atmosphere at a magnetic field strength of 1.5T to 2.2T, and then isostatically pressing the mixed fine powder 1 and the mixed fine powder 2 at a pressure of 140 to 220 MPa to obtain a green body; S6. The green body is subjected to sintering and aging treatment. The green body is vacuum sintered at a sintering temperature of 1045-1065°C and a holding time of 6-10 hours. The green body is then subjected to aging treatment. The aging treatment is a two-stage aging treatment. The primary aging treatment has a temperature of 850-920°C and a holding time of 3-5 hours. The secondary aging treatment has a temperature of 480-520°C and a holding time of 3-5 hours. Thus, a sintered NdFeB magnet is obtained.
[0028] Embodiment 9 comprises the following steps: S1. Obtaining a NdFeB base alloy by vacuum melting, wherein the general chemical formula of the NdFeB base alloy is: (Pr f Nd g ) a Co b Cu c M d B e Fe 100-a-b-c-d-e-f ; Wherein, a, b, c, d, e, f, g are mass percentages, 29.5≤a≤30.5, 0≤b≤2.5, 0.1≤c≤0.4, 0<d≤3, 0.9≤e≤1, f:g=23~28:72~77; M is Zr, Ti and Ga, and Cu:Ga=1:1; S2. Place the NdFeB base alloy into a quick-setting furnace crucible for smelting. Then, under the protection of inert gas argon, place it in an induction furnace at 1480±20℃ and a vacuum degree of 2~10×10 -2Pa conditions, and then rapidly quenched and spun at 1425±20℃ to form a quick-solidified casting sheet with a thickness of 0.28±0.05mm; S3, placing the quick-solidification casting sheet into a hydrogen crushing furnace, absorbing hydrogen at a pressure of 0-2MPa for 2-4h, then dehydrogenating at a temperature of 500-600°C for 6-10h, and finally cooling to obtain coarse powder; S4, mixing a portion of the coarse powder with 0.05%~0.1% antioxidant, stirring evenly with a three-dimensional mixer, and then jet milling under the condition that the oxidizing gas content is 0ppm, and then crushing to obtain a mixed fine powder 1 with a particle size of 3.8±0.1um; at the same time, mixing another portion of the coarse powder with 0.05%~0.1% antioxidant, stirring evenly with a three-dimensional mixer, and then jet milling under the condition that the oxidizing gas content is 0ppm, and then crushing to obtain a mixed fine powder 2 with a particle size of 4.5±0.1um; the mixed fine powder 1 and the mixed fine powder 2 are mixed in a weight percentage of 1:1, and then 0.05%~0.1% lubricant is added, and the mixture is stirred evenly with a three-dimensional mixer for pressing and molding; S5, orienting and molding the mixed fine powder 1 and the fine powder 2 in a nitrogen protective atmosphere at a magnetic field strength of 1.5T to 2.2T, and then isostatically pressing the mixed fine powder 1 and the mixed fine powder 2 at a pressure of 140 to 220 MPa to obtain a green body; S6. The green body is subjected to sintering and aging treatment. The green body is vacuum sintered at a sintering temperature of 1045-1065°C and a holding time of 6-10 hours. The green body is then subjected to aging treatment. The aging treatment is a two-stage aging treatment. The primary aging treatment has a temperature of 850-920°C and a holding time of 3-5 hours. The secondary aging treatment has a temperature of 480-520°C and a holding time of 3-5 hours. Thus, a sintered NdFeB magnet is obtained.
[0029] Embodiment 10 comprises the following steps: S1. Obtaining a NdFeB base alloy by vacuum melting, wherein the chemical formula of the NdFeB base alloy is PrNd 30.2 B 0.9 Zr 0.1 Ti 0.1 Cu 0.18 Co1Al 0.1 Ga 0.18 ; S2, put the NdFeB base alloy into the crucible of the rapid solidification furnace for melting, and then heat it in an induction furnace at 1490℃ and vacuum degree 5×10 -2 The steel was melted under Pa conditions, and then rapidly quenched at 1430℃ to produce a quick-solidified casting sheet with a thickness of 0.29mm. S3, placing the quick-solidification casting sheet into a hydrogen crushing furnace, absorbing hydrogen at a pressure of 2MPa for 3h, then dehydrogenating at a temperature of 520°C for 7h, and finally cooling to obtain coarse powder; S4, mixing a portion of the coarse powder with 0.08% antioxidant, stirring evenly with a three-dimensional mixer, and then jet milling under the condition that the oxidizing gas content is 0ppm, and then crushing to obtain a mixed fine powder 1 with a particle size of 3.8um; at the same time, mixing another portion of the coarse powder with 0.08% antioxidant, stirring evenly with a three-dimensional mixer, and then jet milling under the condition that the oxidizing gas content is 0ppm, and then crushing to obtain a mixed fine powder 2 with a particle size of 4.5um; the mixed fine powder 1 and the mixed fine powder 2 are mixed in a weight percentage of 1:1, and then 0.08% lubricant is added, and the mixture is stirred evenly with a three-dimensional mixer for pressing and molding; S5, orienting and molding the mixed fine powder 1 and the fine powder 2 in a nitrogen protective atmosphere with a magnetic field strength of 2T, and then isostatically pressing the mixed fine powder 1 and the fine powder 2 at a pressure of 200MPa to obtain a green body; S6. The green body is subjected to sintering and aging treatment. It is vacuum sintered at a sintering temperature of 1045°C and a holding time of 6 hours, and then subjected to aging treatment. The aging treatment is a two-stage aging treatment, wherein the temperature of the first aging treatment is 850°C and the holding time is 3 hours, and the temperature of the second aging treatment is 520°C and the holding time is 5 hours, thereby obtaining a sintered NdFeB magnet.
[0030] According to product requirements, the present invention processes the sintered NdFeB magnets of each embodiment into a standard sample column of D10*10 (mm), tests the magnetic properties under the same conditions (same temperature, same humidity, same test equipment, same test coil, etc.), and simultaneously processes the sintered NdFeB magnets of each embodiment into a block of 31.45-20.3-4.8 (mm) as required, and then uses an electronic universal testing machine to perform three-point bending, and tests are performed under the conditions of a span of 20 mm and a test speed of 5 mm / min. The results of the magnetic properties and bending strength of the blank are shown in FIG. Figure 1 Table 1 (blank magnetic properties and flexural strength results).
[0031] The present invention processes the sintered NdFeB magnets of each embodiment into blocks of 31.45-20.3-4.8 (mm) as required, and performs grain boundary penetration according to the same coating powder amount and the same process, and then takes three pieces of each sample to make a D10*4.8 (mm) cylinder, and then tests the magnetic properties (same temperature, same humidity, same test equipment, same test coil, etc.), and the remaining 31.45-20.3-4.8 (mm) blocks are subjected to three-point bending using an electronic universal testing machine, and the test is performed under the conditions of a span of 20 mm and a test speed of 5 mm / min. The magnetic properties and bending strength results after grain boundary penetration are shown below. Figure 2 Table 2 (magnetic properties and flexural strength results after grain boundary penetration).
[0032] pass Figure 1 It can be seen from the test results in Table 1 that the sintered NdFeB magnets prepared in the embodiments of the present invention have very good magnetic properties and also improve their bending strength; specifically: 1. By comparing Examples 1-6, it can be found that under the premise of keeping all the ingredients unchanged, different powder particle sizes have little effect on the magnetic properties, and the bending strength is also similar; 2. Comparing Examples 1-6 with Examples 7-10, it can be found that the magnetic properties do not change much, and Examples 7-10 also improve their bending strength (interlocking effect between powders of different particle sizes); 3. By comparing Examples 1-2, 3-4 and 5-6, and comparing Examples 1, 2, 7, 3, 4, 8, and 5, 6, 9, it can be found that under the premise that the components of the sintered NdFeB magnet remain unchanged, different powder particle sizes have little effect on the magnetic properties, but the bending strength is better as the powder particle size becomes coarser, especially the value of different particle sizes is significantly higher than that of each particle size; 4. Experiments were conducted according to different proportions of Zr, Ti, Cu and Ga elements. Figure 1 The test results in Table 1 show that when the sintered NdFeB magnet composition is Zr:Ti=1:1, Cu:Ga=2.22:1 (Examples 7 and 10), the bending strength is better than that of the components Zr:Ti=1:2 (Example 8) and Cu:Ga=1:1 (Example 9). It can be seen that Examples 7 and 10 are the best examples. 5. In this system, the effect of different powder particle sizes on grain boundary penetration can be basically ignored. When the components are Zr:Ti=1:1 and Cu:Ga=2.22:1, the permeability (the increase of Hcj after grain boundary penetration) is also reduced. At the same time, after grain boundary penetration, the bending strength of the sintered NdFeB magnet is also improved to a certain extent. The reason is that the coating source penetrates into the grain boundary phase through the grain boundary, filling and repairing the discontinuous phase at the boundary.
[0033] The present invention involves only one kind of raw material, quick-setting casting sheet and coarse powder, and the process is simple. There is no need to perform multiple smelting and hydrogen crushing to prepare coarse powder. The single powder particle size increase can greatly improve the bending strength without changing the magnet performance. The operation is simple for production personnel and the production feasibility is extremely high. If a NdFeB magnet with higher bending strength is to be obtained, the proportion of powder materials with multiple powder particle sizes is extremely operable, and the particle size is coarser and the safety is higher.
[0034] In addition, the present invention combines electroplating and chemical vapor deposition to plate a complex nucleation film through grain boundary diffusion technology, which improves the coercive force of the sintered NdFeB permanent magnet while strengthening the grain boundaries, thereby improving the three-point bending strength of the sintered NdFeB permanent magnet.
[0035] The technologies described in the above embodiments can be combined arbitrarily, and as long as they are similar to the technical features herein, they should be considered to be within the scope of the present invention. Therefore, the protection point of the present invention includes but is not limited to keeping the various components unchanged and improving the bending strength of the sintered NdFeB magnet only by changing the powder particle size. If the various improvements or deformations are developed without departing from the concept of the present invention, they should all fall within the scope of protection of the present invention.
[0036] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A high bending strength sintered NdFeB magnet, characterized in that: With the general formula: (Pr f when g ) a Co. b With c M d B e Fe 100-a-b-c-d-e-f ; Wherein, a, b, c, d, e, f, g are mass percentages, 29.5≤a≤30.5, 0≤b≤2.5, 0.1≤c≤0.4, 0<d≤3, 0.9≤e≤1, f:g=23~28:72~77; M is a combination of two or more of Al, Cr, Nb, Zr, Ga, Ti, Mn, Zn, V, and Mo and must contain Ga.
2. A high bending strength sintered NdFeB magnet according to claim 1, characterized in that: With the general formula: (Pr f when g ) a Co. b With c M d B e Fe 100-a-b-c-d-e-f ; Wherein, a, b, c, d, e, f, g are mass percentages, 29.5≤a≤30.5, 0≤b≤2.5, 0.1≤c≤0.4, 0<d≤3, 0.9≤e≤1, f:g=23~28:72~77; M is Zr, Ti and Ga, and Zr:Ti=1:1, Cu:Ga=2.22:
1.
3. A high bending strength sintered NdFeB magnet according to claim 1, characterized in that: With the general formula: (Pr f when g ) a Co. b With c M d B e Fe 100-a-b-c-d-e-f ; Wherein, a, b, c, d, e, f, g are mass percentages, 29.5≤a≤30.5, 0≤b≤2.5, 0.1≤c≤0.4, 0<d≤3, 0.9≤e≤1, f:g=23~28:72~77; M is Zr, Ti and Ga, and Zr:Ti=1:
2.
4. A high bending strength sintered NdFeB magnet according to claim 1, characterized in that: With the general formula: (Pr f when g ) a Co. b With c M d B e Fe 100-a-b-c-d-e-f ; Wherein, a, b, c, d, e, f, g are mass percentages, 29.5≤a≤30.5, 0≤b≤2.5, 0.1≤c≤0.4, 0<d≤3, 0.9≤e≤1, f:g=23~28:72~77; M is Zr, Ti and Ga, and Cu:Ga=1:
1.
5. A method for preparing a high flexural strength sintered NdFeB magnet, characterized in that: The steps include: S1. Obtaining a NdFeB base alloy by vacuum melting, wherein the general chemical formula of the NdFeB base alloy is: (Pr f Nd g ) a Co b Cu c M d B e Fe 100-a-b-c-d-e-f ; Wherein, a, b, c, d, e, f, g are mass percentages, 29.5≤a≤30.5, 0≤b≤2.5, 0.1≤c≤0.4, 0<d≤3, 0.9≤e≤1, f:g=23~28:72~77; M is a combination of two or more of Al, Cr, Nb, Zr, Ga, Ti, Mn, Zn, V, Mo and must contain Ga; S2, placing the NdFeB base alloy obtained in step S1 into a rapid solidification furnace crucible for smelting, and then rapidly quenching to obtain a rapid solidification casting sheet; S3, placing the rapidly solidified casting sheet into a hydrogen crushing furnace, performing dehydrogenation treatment, and cooling to obtain a coarse powder; S4, mixing the coarse powder with the antioxidant, stirring evenly with a three-dimensional mixer, and then jet milling to obtain fine powder with a particle size of 3.7um to 4.6um, adding a lubricant to the fine powder, and stirring evenly with a three-dimensional mixer; S5, orienting the fine powder with lubricant added in a nitrogen atmosphere with a magnetic field strength of 1.5T to 2.2T, and then isostatically pressing to obtain a green body; S6. The green body is subjected to sintering and aging treatment to obtain a sintered NdFeB magnet.
6. The method for preparing a high bending strength sintered NdFeB magnet according to claim 5, characterized in that: In step S1, the general chemical formula of the NdFeB substrate alloy is: (Pr f Nd g ) a Co b Cu c M d B e Fe 100-a-b-c-d-e-f ; Wherein, a, b, c, d, e, f, g are mass percentages, 29.5≤a≤30.5, 0≤b≤2.5, 0.1≤c≤0.4, 0<d≤3, 0.9≤e≤1, f:g=23~28:72~77; M is Zr, Ti and Ga, and Zr:Ti=1:1, Cu:Ga=2.22:
1.
7. The method for preparing a high bending strength sintered NdFeB magnet according to claim 5, characterized in that: In step S1, the general chemical formula of the NdFeB substrate alloy is: (Pr f Nd g ) a Co b Cu c M d B e Fe 100-a-b-c-d-e-f ; Wherein, a, b, c, d, e, f, g are mass percentages, 29.5≤a≤30.5, 0≤b≤2.5, 0.1≤c≤0.4, 0<d≤3, 0.9≤e≤1, f:g=23~28:72~77; M is Zr, Ti and Ga, and Zr:Ti=1:
2.
8. The method for preparing a high bending strength sintered NdFeB magnet according to claim 5, characterized in that: In step S1, the general chemical formula of the NdFeB substrate alloy is: (Pr f Nd g ) a Co b Cu c M d B e Fe 100-a-b-c-d-e-f ; Wherein, a, b, c, d, e, f, g are mass percentages, 29.5≤a≤30.5, 0≤b≤2.5, 0.1≤c≤0.4, 0<d≤3, 0.9≤e≤1, f:g=23~28:72~77; M is Zr, Ti and Ga, and Cu:Ga=1:
1.
9. The method for preparing a high bending strength sintered NdFeB magnet according to claim 6, characterized in that: In step S4, a portion of the coarse powder is mixed with 0.05%~0.1% antioxidant, and after being stirred evenly in a three-dimensional mixer, it is subjected to jet milling under the condition that the oxidizing gas content is 0ppm, and after being crushed, a mixed fine powder 1 with a particle size of 3.8±0.1um is obtained; at the same time, another portion of the coarse powder is mixed with 0.05%~0.1% antioxidant, and after being stirred evenly in a three-dimensional mixer, it is subjected to jet milling under the condition that the oxidizing gas content is 0ppm, and after being crushed, a mixed fine powder 2 with a particle size of 4.5±0.1um is obtained; the mixed fine powder 1 and the mixed fine powder 2 are mixed in a weight percentage of 1:1, and then 0.05%~0.1% of a lubricant is added, and the mixture is stirred evenly in a three-dimensional mixer.
10. A method for preparing a high bending strength sintered NdFeB magnet according to any one of claims 5 to 9, characterized in that: In step S5, the fine powder to which the lubricant is added is oriented and formed in a magnetic field strength of 1.5T~2.2T and a nitrogen protective atmosphere, and isostatically pressed at a pressure of 140MPa~220MPa to obtain a green body; in step S6, the green body is vacuum sintered at a sintering temperature of 1045℃~1065℃ and a holding time of 6h~10h, and then aged to obtain a sintered NdFeB magnet.